Realizing Student, Faculty, and Institutional Outcomes at Scale: Institutionalizing Undergraduate Research, Scholarship, and Creative Activity Within Systems and Consortia. Issue 169 (March 2015) - Malachowski, Mitchell; Osborn, Jeffrey M.; Karukstis, Kerry K.; Ambos, Elizabeth L.
Abstract : This chapter reviews the evidence for the effectiveness of undergraduate research as a student, faculty, and institutional success pathway, and provides the context for the Council on Undergraduate Research's support for developing and enhancing undergraduate research in systems and consortia. The chapter also provides brief introductions to each of the chapters in the theme volume.